FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN - Maydica Rossa Arsianto; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2013)
This paper aims to test and provide empirical evidence about the influence of auditor reputation, disclosure, audit tenure, firm size, and the previous year's audit opinion to the going concern audit opinion. At this point the auditor should be able to disclose an entity's business continuity and be able to predict the company's ability to carry out its business. Population of this research is manufacturing companies listed on Indonesian Stock Exchange (IDX) between 2007 to 2011. Research sample amounts to 53 companies acquired by purposive sampling method, with observation period of 5 years. Data were analyzed by using logistic regression. Based on this research can be concluded that audit tenure, size of the company, and previous year's audit opinion significantly influence the going concern audit opinion. While the auditor reputation and disclosure did not significantly influence the going concern audit opinion.